2010
DOI: 10.1016/j.jacc.2009.09.065
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences in Myocardial Remodeling

Abstract: Sex has a profound impact on myocardial remodeling, which is defined as the molecular and cellular events after an injury to the myocardium (i.e., necrosis, pressure overload, volume overload, and aging) leading to a change in shape, dimension, and function of cardiac chambers. Indeed, experimental studies and post-mortem and observational clinical studies suggest the presence of important differences in myocardial remodeling between females and males in response to different types of injures including aging, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
179
2
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(200 citation statements)
references
References 74 publications
14
179
2
5
Order By: Relevance
“…In our study, women had a more favorable course of LV remodeling following STEMI, which could be related to gender differences in levels of sex hormones [23]. Cavasin et al have demonstrated that estrogen and testosterone play different and opposing roles in the development of heart failure and long-term LV remodeling following MI.…”
Section: Discussionsupporting
confidence: 48%
“…In our study, women had a more favorable course of LV remodeling following STEMI, which could be related to gender differences in levels of sex hormones [23]. Cavasin et al have demonstrated that estrogen and testosterone play different and opposing roles in the development of heart failure and long-term LV remodeling following MI.…”
Section: Discussionsupporting
confidence: 48%
“…This confirms sex differences previously observed in the I‐PRESERVE registry,5 and for the first time identifies race‐related differences with regard to outcomes in patients with concurrent HFpEF and atrial fibrillation. Sex‐ and race‐related differences in left ventricular adaptation to stressors have previously been demonstrated, as women40, 41, 42 and blacks43, 44, 45 have a predilection for developing concentric left ventricular hypertrophy and greater diastolic dysfunction compared with men and whites. Whether these differences contribute to an increased vulnerability to atrial fibrillation among women and blacks is not well understood and warrants investigation.…”
Section: Discussionmentioning
confidence: 95%
“…Prognostic value, however, seems equally strong for male and female subjects, so that gender-specific elevations carry equal prognostic importance. The gender interaction warrants further study, as for instance ventricular remodelling differs considerably between male and female subjects [32], and the role of galectin-3 in this may be of importance.…”
Section: Discussionmentioning
confidence: 99%